Desarrollo de una plataforma para la investigación dentro de mundos virtuales - Herrera Rosales, David Abel (My University, 2012)
Desarrollo de una plataforma para la investigación dentro de mundos virtuales
Desarrollo de una plataforma para la investigación dentro de mundos virtuales
Keywords: Desarrollo de una plataforma para la investigación dentro de mundos virtuales